Effect of Eucalyptus Monoculture on the Status of Soil Organic Matter in Natural Sal (Shorea Robusta) Zone in Doon Valley - Singhal, R. M.; Banerjee, S. P.; Pathak, T. C. (Indian Forester, 1975)
Trend in the changes in peroxidisable, alkali-extractable, and acid-hydrolysable fractions of the soil organic matter under Eucalyptus monoculture and surrounding natural sal in the course of a quinquennium reveals that the former humifies easier and faster. Oxidisability of resistant organic matter of the surface samples increases under both but the non-peroxidisable carbon decreases in all the layers under Eucalyptus as compared to surrounding sal. Optical densities of the alkali- extractable organic fraction, in general, increases and more so in the surface layers, reflecting certain changes in the nature of the organic matter returned during this period. Translocation of the humified material is more pronounced under Eucalyptus although to a limited depth. Soil organic matter under Eucalyptus is more hydrolysable, and non-hydrolysable fractions decrease very significantly under sal as compared to Eucalyptus.